1997
DOI: 10.1097/00042560-199708150-00007
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of HIV-Related Mortality Is Associated With Selenium Deficiency

Abstract: To determine the independent contribution of specific immunologic and nutritional factors on survival in HIV-1 disease, CD4 cell count, antiretroviral treatment, plasma levels of vitamins A, E, B6, and B12 and minerals selenium and zinc were considered in relation to relative risk for HIV-related mortality. Immune parameters and nutrients known to affect immune function were evaluated at 6-month intervals in 125 HIV-1-seropositive drug-using men and women in Miami, FL, over 3.5 years. A total of 21 of the HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
226
2
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(248 citation statements)
references
References 32 publications
14
226
2
6
Order By: Relevance
“…Work carried out by Baum and co-workers at the University of Miami showed that selenium-deficient HIV patients are 19.9 times more likely (95% CI 5.52-71.9; p<0.0001) to die from HIV-related causes than those with adequate levels. 18 Selenium deficiency is defined by Baum as a plasma level at or below 85 mcg/L, a level not attained in many northern European countries (see below), e.g. a mean level of 60 mcg/L was found in a recent Scottish study.…”
Section: Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work carried out by Baum and co-workers at the University of Miami showed that selenium-deficient HIV patients are 19.9 times more likely (95% CI 5.52-71.9; p<0.0001) to die from HIV-related causes than those with adequate levels. 18 Selenium deficiency is defined by Baum as a plasma level at or below 85 mcg/L, a level not attained in many northern European countries (see below), e.g. a mean level of 60 mcg/L was found in a recent Scottish study.…”
Section: Viral Infectionmentioning
confidence: 99%
“…15,18 Elucidation of the importance of novel viral selenoproteins may improve our understanding of HIV. 14 Baum With regard to cancer, an extended repeat of the NPC trial is now planned with cohorts in three European countries and the US, to see if the reduction of cancer risk and mortality with selenium supplementation previously observed can be replicated in other population groups.…”
Section: Selenium Research -The Way Aheadmentioning
confidence: 99%
“…Yu et al (63) , Bjelakovic et al (64) In US patients with relatively low Se status (plasma Se < 85 mg/l) HIV infection progresses more rapidly to AIDS with higher mortality Baum et al (65) , Campa et al (66) In a Tanzanian observational study of 949 HIV-positive pregnant women mortality decreases with increase in plasma Se ( > 85 mg/l) over 5-year follow-up period Kupka et al (67) Cancer Inverse relationship between crop and human Se status and cancer incidence in North America…”
Section: Antiviral Effects and Hivmentioning
confidence: 99%
“…In some studies, low-serum zinc was related to progression to AIDS (Graham et al, 1991), decreases in CD4 cell counts (Baum et al, 2003) and mortality (Baum et al, 1997a(Baum et al, , 2003, and low-dietary intake was associated with decreased survival (Baum et al, 2003). Conversely, another prospective study reported an inverse association between zinc consumption and survival of HIV-positive adults (Tang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%